Peningkatan Pengetahuan Dan Motivasi Dalam Meneguhkan Dasar Pemasaran (Pemasaran & Pemasaran Digital) Melalui Guru Tamu Dalam Mempersiapan Diri Siswa SMK Kartika X-2 Jakarta Selatan Guna Menjalani Dunia Industri - Totok Priyono (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2023)
Technological development, changes in people's preferences, and the dynamics of world development that affect the economy and state policies, as well as other influences that encourage innovation are important factors in preparing workforce competencies. The Marketing Online Business departement prepares students with online business and marketing skills.  Kartika X-2 Vocational High School, South Jakarta is one of the providers of formal vocational education with one of the areas of expertise being Business and Management with a major in Marketing Online Business. Even though it has an adequate curriculum in preparing student competencies, the motivation of each student is different in completing competency achievement.  Motivation is needed to encourage student behavior to achieve competency standards, with the personal conditions of each student being different.  It is necessary to provide knowledge of industrial workers in the field of marketing to be important to confirm and serve as a comparison between the teaching process in schools and marketing work in industry. Guest Teachers provide material that reinforces the basis of marketing, goal setting, student soft skill readiness which increases student motivation in achieving competency standards in order to work in the industrial world.